A secure rubber supply chain management system based on hyperledger fabric blockchain: a use case in Cambodia - Keo, Ratanak; Firdaus, Muhammad; Rhee, Kyung-Hyune (Frontiers in Blockchain, 2025)
Conventional traceability systems in Cambodian agriculture, such as rubber, rice, and cassava supply chain management, often fail to provide timely data and fair market prices, leading to mistrust among stakeholders, exploitation by intermediaries, and hindering progress towards ethical sourcing and sustainable practices. This paper demonstrates the potential of integrating blockchain, IoT, the InterPlanetary File System (IPFS), and Differential Privacy (DP) techniques to empower Cambodian rubber farmers. By leveraging Hyperledger Fabric (HLF), the proposed system enhances transparency and facilitates fair pricing by forming decentralized rubber traceability from supplier to consumer. Integration with IPFS ensures secure and accessible data storage, while differential privacy techniques protect confidential data during information sharing. Our approach facilitates a model for other developing countries aiming to modernize agricultural distribution networks. Numerical results demonstrate that our system achieved the overall performance objectives, including transaction send rates, transaction throughput, and transaction latency. However, the results highlight a trade-off between privacy and performance in blockchain-based agricultural traceability systems. Specifically, while implementing differential privacy techniques enhances data confidentiality, it can slightly reduce system efficiency and scalability compared to configurations without privacy measures.